The important role of circular dorsal ruffles in the internalization and trafficking of the insulin receptor - Araújo-Correia, Ana Margarida (2021)
Type 2 diabetes mellitus (T2DM) is one of the most common chronic diseases worldwide, mainly caused by excessive body weight and a sedentary lifestyle. This disorder is increasing exponentially, affecting 425 million people, a number expected to increase up to 692 million by 2045. Although the pathogenesis of T2DM has been thoroughly studied, the available treatment options are still scarce. Insulin resistance is a hallmark for T2DM and occurs when the body cannot respond appropriately to circulating insulin levels. It is characterized by hyperinsulinemia, hyperglycemia and hypertriglyceridemia. Importantly, insulin resistance (IR) is not limited to the liver and skeletal muscle, also affecting organs like the adipose tissue, heart, kidney and brain. Thus, diabetes is viewed nowadays as a complex disorder affecting multiple organ systems. Subclinical chronic inflammation appears to be the common denominator between IR and T2DM, although the molecular mechanisms underlying this connection are still controversial. The liver is a central metabolic organ in regulating whole-body homeostasis and energy metabolism. It helps maintaining fasting glucose levels through gluconeogenesis, as in the fed state converts glucose into glycogen and lipids for storage. Insulin has a central role in controlling hepatic energy metabolism, suppressing glucose production while stimulating lipogenesis. At a cellular level, the molecular mechanism underlying the onset of IR is the impairment of the insulin signaling pathway in hepatocytes, myocytes and adipocytes among others. The insulin signaling cascade is a complex and broad pathway that at each step contains several molecules or isoforms capable of transducing the signal, each with distinct but overlapping functions. Besides its main target pathway, insulin also activates a number of downstream cascades that intertwine and modulate each other. Impairing the activity of any single component, from insulin binding to the molecules involved in insulin receptor (InsR) internalization and trafficking and signal propagation, can lead to IR. Cells undergo active remodeling in response to a variety of physiological and pathological stimuli. Importantly, circular dorsal ruffle (CDR) formation emerged as an important type of membrane reorganization involved in RTK internalization. CDR-mediated macropinocytosis is a selective process, as only ligand-bound receptors are internalized. This is a widespread endocytic route, as these structures form in a variety of cell types upon stimulation with different growth factors, strongly supporting their relevance. InsR internalization is a crucial step for insulin signaling pathway activation, insulin metabolism and receptor downregulation at the plasma membrane, avoiding deleterious effects of an overactive pathway. Moreover, InsR internalization is especially important in the liver, since it determines peripheral insulin bioavailability, through the balance between insulin secretion and clearance, hence maintaining glucose homeostasis in the target organs. Although several studies show clathrin-mediated endocytosis as the main pathway for InsR internalization, these studies are quite vague and do not focus on the relevance of receptor recycling and/or degradation, and on how this pathways may be altered in IR. Knowing that CDR-mediated internalization is able to remove large amounts of activated receptors from the plasma membrane, we hypothesized that CDRs are a non-canonical endocytic pathway involved in the internalization and recycling/degradation of the InsR. The overall goal of this work was to understand the role for CDR-mediated macropinocytosis in InsR internalization, in physiological and pathophysiological contexts. The specific aims were to determine whether insulin promotes CDR formation in these cells; to understand if the InsR is sequestered and internalized through CDR-mediated macropinocytosis upon insulin stimulation; to study the role of CDR formation in hepatocytes; and finally, to explore the impact of chronic high insulin levels and iNOS overexpression in insulin-mediated CDR formation. For the first aim of this study, we used Hepa 1-6 mouse hepatoma cells stimulated with increasing insulin concentrations, to assess CDR formation. We demonstrate for the first time that insulin treatment stimulates CDR formation in hepatocytes, as early as one minute after insulin addition to the media, in a time- and concentration-dependent manner. CDR formation reaches a peak 5 minutes after stimulation, returning to close to basal levels at 60 minutes after treatment. The same pattern was observed upon intermediate and low insulin concentrations, although the increase was not as striking. Signaling events mediated by ligand binding to RTKs are a very fast process, which we confirmed by analyzing insulin signaling pathway activation through InsR and Akt phosphorylation. As expected, in the absence of an insulin stimulus, mimicking a fasting state, InsR and Akt are not phosphorylated; on the other hand, in a postprandial state scenario as insulin levels increase, both receptor and Akt become phosphorylated as early as one minute after insulin treatment, concomitant with CDR formation. We also evaluated the formation of CDRs in mouse primary hepatocytes, which are more representative of the liver physiology. We confirmed that insulin also stimulates CDR formation in these cells. The remarkable increase in CDR formation after insulin stimulation led us to our next aim. The finding that endogenous InsR localizes to CDRs upon insulin stimulation, demonstrated by immunofluorescence, strongly suggests that InsR internalization is mediated by these structures. The InsR is mostly located at the plasma membrane when insulin is absent, being sequestered to CDRs upon insulin treatment. The presence of the receptor in these structures starts decreasing at 30 minutes, being completely internalized 60 minutes after stimulation. Live-imaging corroborates these findings, as we were able to observe the formation of CDRs at the dorsal surface of InsR-GFP transfected cells and the localization of InsR to the structures. Next, we investigated the impact of WAVE1 silencing, a protein involved in CDR ring formation, in insulin signaling. We confirmed by immunofluorescence that WAVE1 silencing robustly decreases insulin-stimulated CDR formation, and also decreases Akt Ser473 and Thr398 phosphorylation, indicating an impairment in insulin signaling. We finally addressed the consequence of chronic high insulin exposure and iNOS overexpression a characteristic of sub-clinical inflammation in CDR formation and insulin signaling. In cells incubated in conditions mimicking hyperinsulinemia for 48 hours, we observed a decrease in CDR formation. Aa curious aspect is that this decrease is drastic in cells that were serum-starved without insulin in the media, as in cells where insulin was always present. Finally, increased NO concentrations also abrogate CDR formation, further impairing insulin signaling by decreasing phosphorylated levels of InsR and Akt phosphorylation. We propose that CDR-mediated InsR endocytosis works alongside other endocytic pathways, mediating receptor internalization. We showed that CDR formation is a common pathway present in insulin-sensitive tissues and that its abrogation impairs insulin signaling activation. Furthermore, pathophysiological conditions such as hyperinsulinemia and sub-clinical inflammation dramatically abrogate CDR formation. Endocytosis through CDRs might allow the cells to rapidly recycle the InsR back to the plasma membrane or to downregulate signal, as this pathway internalizes large amounts of activated receptors. Further studies are necessary to better understand this mechanism and its influence on InsR recycling/degradation.